2017
DOI: 10.1590/1413-81232017229.12982016
|View full text |Cite
|
Sign up to set email alerts
|

Do not forget culture when implementing mental health interventions for violence survivors

Abstract: Do not forget culture when implementing mental health interventions for violence survivorsNão se esqueça da cultura quando for implementar intervenções mentais em saúde para sobreviventes da violência

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Therefore, it is necessary to fulfill these needs, by means of human rights restoration processes 22,29,30 . Also, it is need to understand the importance of this local context to create valid instruments and locally appropriate interventions 31 , taking into account healing, living and coping traditions of Afro-Colombian communities 32 . The study has some limitations: Findings cannot be generalized different cultural settings, but it helps to implement community-based interventions for violence survivors in similar contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to fulfill these needs, by means of human rights restoration processes 22,29,30 . Also, it is need to understand the importance of this local context to create valid instruments and locally appropriate interventions 31 , taking into account healing, living and coping traditions of Afro-Colombian communities 32 . The study has some limitations: Findings cannot be generalized different cultural settings, but it helps to implement community-based interventions for violence survivors in similar contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Research on mental health interventions in post-conflict contexts posits the need of trained psychologists who can support dissemination and implementation of evidence-based effective health care approaches (Murray et al, 2014). Further, some communities require community interventions that consider their cultural characteristics and their coping mechanisms (Bonilla-Escobar et al, 2017). In particular, post-conflict contexts require professionals who are prepared to work with culturally diverse populations, recognizing the victim's multiple local knowledges and cultural practices, and offering an empathetic and rigorous service (Osorio-Cuellar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[6] There is limited information about displacement in Colombia including the average length of displacement, the different traumatic experiences suffered by victims of the armed conflict, or the effect of interventions on mental health of victims. [79] Previous research has shown that Afro-Colombian victims of violence experience symptoms of post-traumatic stress disorder (PTSD), depression, and anxiety. [913] Despite this, few psychosocial services are readily available for survivors of the conflict.…”
Section: Introductionmentioning
confidence: 99%
“…This was considered as the easiest way to access victims, promoting confident relationships between participants and LPCW. [7, 2325]…”
Section: Introductionmentioning
confidence: 99%